Medidas de restauración del manglar hizophora mangle<(mangle rojo) en asentamientos de camaroneras en el archipiélago de jambelí - Loayza Chila, Mayra Alexandra (Machala : Universidad Técnica de Machala, 2021)
The present work investigates the state of mangrove ecosystems in Ecuador, specifically in the province of Oro, in the Jambelí Archipelago, and the damage caused by aquaculture; its displacement and development, the effects caused by the cutting of mangroves and possible affectations to the species. The search for information and review of scientific and technical literature of various works at the global and local level, interpreted that being one of the most important ecosystems in the world has not been well standardized, socialized and fulfilled the measures that have been implemented for more than 50 years. Mangroves in Ecuador and in the province of El Oro have been devastated by approximately 40% due to shrimp farming activities. In addition, there are human populations, settlements and urbanizations that are developing more and more and their growth in this area is not favorable since this has contributed to the reduction and displacement of biodiversity in estuarine species. The implementation of measures that are considered optimal for the reduction of biodiversity loss referring to estuarine ecosystems are not well implemented and above all there are no programs that are directly focused on shrimp and mangrove cultivation, most are focused on the repopulation of conch, crabs and other species, but not on direct damage to the habitat of these, and with a direct aim to deterioration by shrimp farming and its questionable management.
El presente trabajo indaga sobre el estado de los ecosistemas de manglar en el Ecuador específicamente en la provincia de Oro, en el Archipiélago de Jambelí, y el daño que ha causado la Acuacultura; sus desplazamientos y su desarrollo, los efectos causados por la tala de manglares y posibles afectaciones a las especies. La Búsqueda de información y revisión de literatura científica y técnica de varios trabajos a nivel mundial y local, interpretan que siendo uno de los ecosistemas más importantes en el mundo no ha sido bien estandarizadas, socializadas y cumplidas las medidas que se ha implementado durante más de 50 años. Los manglares en el Ecuador y la provincia del Oro han sido devastados aproximadamente un 40% por la actividad camaronera, adicionalmente existen; poblaciones humanas, asentamientos y urbanizaciones que cada vez se van desarrollando más y su crecimiento en esta zona no es favorable ya que esto ha contribuido a la reducción y desplazamiento de la biodiversidad en especies estuarinas. La implementación de las medidas que se consideran óptimas para la reducción de pérdida de biodiversidad haciendo referencia a los ecosistemas estuarinos que no están bien implementados y sobre todo no hay programas que estén centrados directamente al cultivo de camarón y manglar, la mayoría está enfocada a la repoblación de concha, cangrejos y otras especies, pero no al daño directo al hábitat de estas, y con fin directo a deterioros por la camaronicultura y sus cuestionados manejos.
Keywords: MANGLAR; ROJO; ECOSISTEMAS; JAMBELÍ